Performance evaluation of nursing students following competency-based education. (January 2015) - Fan, Jun-Yu; Wang, Yu Hsin; Chao, Li Fen; Jane, Sui-Whi; Hsu, Li-Ling
Summary: Background: Competency-based education is known to improve the match between educational performance and employment opportunities. Objectives: This study examined the effects of competency-based education on the learning outcomes of undergraduate nursing students. Design: The study used a quasi-experimental design. Participants: A convenience sample of 312 second-year undergraduate nursing students from northern and southern Taiwan participated in the study. Methods: The experimental group ( n = 163) received competency-based education and the control group received traditional instruction ( n = 149) in a medical–surgical nursing course. Outcome measures included students' scores on the Objective Structured Clinical Examination, Self-Evaluated Core Competencies Scale, Metacognitive Inventory for Nursing Students questionnaire, and academic performance. Results: Students who received competency-based education had significantly higher academic performance in the medical–surgical nursing course and practicum than did the control group. Required core competencies and metacognitive abilities improved significantly in the competency-based education group as compared to the control group after adjusting for covariates. Conclusions: Competency-based education is worth implementing and may close the gap between education and the ever-changing work environment.